Factors Predicting Time to TSH Normalization and Persistence of TSH Suppression After Total Thyroidectomy for Graves' Disease - Paragliola, Rosa Maria; Di Donna, Vincenzo; Locantore, Pietro; Papi, Giampaolo; Pontecorvi, Alfredo; Corsello, Salvatore Maria (Frontiers in Endocrinology, 2019)
Abstract Hyperthyroidism related to Graves’ disease is associated with a suppression of TSH values which may persist after surgery in spite of a LT4 replacement therapy at non-TSH-suppressing doses. The aim of this retrospective study was to evaluate the time to TSH normalization in a group of patients who underwent total thyroidectomy for Graves’ disease receiving a LT4 therapy dose regimen based on a previously published nomogram, and to identify possible correlations between the time to normalization of post-operative TSH values and preoperative clinical and biochemical parameters. 276 patients affected by Graves’ disease who underwent surgery between 2010 and 2015, were retrospectively evaluated for clinical and biochemical parameters as well as post-surgical LT4 treatment regimen. Of the 276 subjects, 174 had initiated LT4 dosage corresponding to a previously published nomogram, and of these, 98 patients were included in our statistical analysis. TSH and FT4 were evaluated at the first post-operative assessment and during follow up until the normalization of TSH values was achieved, and then included in the analysis During the first post-operative evaluation 2 months after surgery, 59/98 patients had TSH values in the normal range (0.4 to 4.0 mcU/ml), while 39/98 patients had a TSH value < 0.4 mcU/mL. The persistence of post-operative TSH levels < 0.4 mcU/ml was significantly correlated (p=0.022) with longer duration of the disease. The value of anti-TSH receptor autoantibodies (TrAb) at the diagnosis of hyperthyroidism, significantly correlated (p=0.002) with the time to TSH normalization in the group of patients with TSH < 0.4 mcU/ml at first control. This retrospective analysis confirms that in subjects who have undergone thyroidectomy for Graves’ disease, time to normalization of TSH may be prolonged. Hence, the role of TSH as the “gold standard” to assess the appropriate LT4 replacement therapy regimen during the initial months following surgery may need to be reconsidered.